2017
DOI: 10.1111/his.13158
|View full text |Cite
|
Sign up to set email alerts
|

Anal verrucous carcinoma is not related to infection with human papillomaviruses and should be distinguished from giant condyloma (Buschke–Löwenstein tumour)

Abstract: Our results suggest that anal VC, similarly to VC at other sites, is not associated with HPV infection, and must be distinguished from BLT, which is associated with low-risk HPV. Only with well-set diagnostic criteria will it be possible to ascertain clinical behaviour and optimal treatment for both lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
0
19
0
2
Order By: Relevance
“…Multiple studies have shown that unlike giant condylomas, which consistently harbor HPV, anogenital verrucous carcinomas diagnosed on the basis of strict histopathologic criteria (see below) are predominantly negative for HPV. 24,25,[28][29][30] These findings support distinct pathogenetic pathways in verrucous carcinoma and giant condyloma acuminatum, and that they should be considered separate entities. Similar to other HPV-negative SCCs of the anogenital tract, verrucous carcinoma is associated with chronic inflammatory conditions such as lichen sclerosus and lichen simplex chronicus, which play a key role in its pathogenesis.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Multiple studies have shown that unlike giant condylomas, which consistently harbor HPV, anogenital verrucous carcinomas diagnosed on the basis of strict histopathologic criteria (see below) are predominantly negative for HPV. 24,25,[28][29][30] These findings support distinct pathogenetic pathways in verrucous carcinoma and giant condyloma acuminatum, and that they should be considered separate entities. Similar to other HPV-negative SCCs of the anogenital tract, verrucous carcinoma is associated with chronic inflammatory conditions such as lichen sclerosus and lichen simplex chronicus, which play a key role in its pathogenesis.…”
mentioning
confidence: 76%
“…However, this view has been challenged by the frequent detection of HPV in giant condylomas but rarely in verrucous carcinomas. 24,25 As in ordinary condyloma acuminatum, giant condylomas usually harbor HPV 6 and 11. 24 Recurrence rate is high, 21 and malignant transformation to invasive SCC has been reported in more than 50% of cases, most commonly in HIV-positive patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, one of the hallmarks of these aggressive tumors is their potential to recurrencereported to be as high as 65%. [9][10][11] In certain cases, the use of chemoradiation or radiation alone (similar regimen to squamous cell carcinoma) can be utilized in a neoadjuvant fashion. The goal is to downsize the tumor to be able to achieve negative margins.…”
Section: Perianal Squamous Cell Carcinomamentioning
confidence: 99%
“…Гигантская кондилома Бушке-Левенштейна (веррукозный рак, веррукозная карцинома, опухоль Бушке-Левенштейна) -заболевание аногенитальной области, вызываемое передающимся половым путем вирусом папилломы человека (ВПЧ) преимущественно 6-го или 11-го типа, характеризующееся наличием обширных сливающихся массивных вегетаций по типу «цветной капусты», прогрессирующим инвазивным ростом и в то же время доброкачественной гистологической картиной [1][2][3]. Некоторые зарубежные авторы разделяют понятия «веррукозная карцинома» и «гигантская кондилома Бушке-Левенштейна», считая, что веррукозная карцинома перианальной области не ассоциирована с ВПЧ [4]. Впервые эта опухоль на половом члене была описана Buschke и Löwenstein в 1925 г.…”
unclassified